Granulocyte-colony-stimulating factor-producing metaplastic carcinoma of the breast with significant elevation of serum interleukin-17 and vascular endothelial growth factor levels - Fukui, Yukiko (Int Cancer Conf J, 2018)
Granulocyte-colony-stimulating factor (G-CSF) production in carcinomas is associated with a very aggressive phenotype. Interleukin (IL)-17 secreted from tumor-infiltrating lymphocytes induces the production of G-CSF and vascular endothelial growth factor (VEGF) in cancer tissue. We present a case of a G-CSF-producing metaplastic breast carcinoma (MpBC) accompanied by systemic elevation of IL-17 and VEGF levels. A 56-year-old woman presented with a rapidly growing tumor measuring > 10 cm in her left breast. Core needle biopsy confirmed the diagnosis as MpBC with triple-negative features. Diffuse fluorodeoxyglucose uptake in the long bones and marked leukocytosis suggested that the G-CSF was produced by the primary tumor, which showed upregulated G-CSF mRNA and protein levels. Multiplex cytokine assessment identified increased serum IL-17, VEGF, and G-CSF levels. After radical mastectomy and skin grafting, the leukocyte count and serum G-CSF, IL-17, and VEGF levels were normalized. She underwent postmastectomy radiotherapy (50 Gy/25 Fr) and adjuvant chemotherapy (90 mg/m(2) of epirubicin and 600 mg/m(2) of cyclophosphamide followed by 80 mg/m(2) of paclitaxel) and is alive without recurrence. This is the first in vivo observation that describes the systemic elevation of IL-17 and VEGF levels with concomitant G-CSF production. Further research is warranted to study the IL-17/G-CSF/VEGF axis as a potential therapeutic target for this aggressive type of breast cancer.